2010
DOI: 10.1523/jneurosci.3950-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Microglia Depends on Na+/H+Exchange-Mediated H+Homeostasis

Abstract: Hϩ extrusion is important for sustained NADPH oxidase activation after "respiratory" burst in macrophage/microglia activation. In this study, we investigated the role of Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(133 citation statements)
references
References 45 publications
7
125
1
Order By: Relevance
“…2E). In microglia and other immune cells, the H + generated by NOX2 activity is released to the extracellular space through both the voltage-sensitive proton channel Hv1 and the Na + /H + exchanger NHE1, and inhibition of either process causes intracellular acidification and resultant cessation of NOX2 activity (21)(22)(23). A distinction between Hv1 and NHE1 is that protons released through Hv1 relieve the plasma membrane depolarization caused by intracellular H + accumulation, whereas Na + /H + exchange is electroneutral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2E). In microglia and other immune cells, the H + generated by NOX2 activity is released to the extracellular space through both the voltage-sensitive proton channel Hv1 and the Na + /H + exchanger NHE1, and inhibition of either process causes intracellular acidification and resultant cessation of NOX2 activity (21)(22)(23). A distinction between Hv1 and NHE1 is that protons released through Hv1 relieve the plasma membrane depolarization caused by intracellular H + accumulation, whereas Na + /H + exchange is electroneutral.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced sodium accumulation in NHE1 +/− neurons may promote neuronal survival (29), and reduced sodium accumulation in nonneuronal cells limits brain edema (40). Moreover, suppression of NOX2 activation by NHE1 or Hv1 inhibition in microglia inhibits the innate immune response, and may thereby promote neuronal survival in the postischemic interval (21)(22)(23).…”
Section: +mentioning
confidence: 99%
“…This increase in [Na + ] i and cell swelling are significantly reduced either with HOE 642 treatment or in NHE-1 -/-astrocytes (Kintner et al, 2004). Using the HAIR model in astrocytes, we found a similar increase in [Na + ] i which could be abolished by the NHE-1 inhibitor HOE 642 (Kintner et al, 2007b (Liu et al, 2010). The elevation in NHE-1-mediated H + extrusion prevents intracellular acidosis, allowing for sustained NADPH oxidase function (Liu et al, 2010).…”
Section: Cell Culturesmentioning
confidence: 73%
“…We subsequently revealed that focal cerebral ischemia triggers a transient stimulation of the extracellular signal-regulated kinase/p90 ribosomal S6 kinase (ERK/p90 RSK ) pathway that contributes to ischemic damage in part via phosphorylation of NHE-1 protein (Manhas et al, 2010). The NHE-1-mediated [Na + ] i overload causes reverse function of the Na + /Ca 2+ exchanger, elevating [Ca 2+ ] i and enhancing the p38 mitogen-activated protein kinase (MAPK) and/or nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) (Liu et al, 2010). NHE-1 activity also plays a detrimental role in mitochondrial Ca 2+ overload and mitochondrial dysfunction after ischemia as evidenced by attenuation of ischemia-induced cytochrome C release from mitochondria after NHE-1 inhibition (Wang et al, 2008).…”
Section: Focal Ischemiamentioning
confidence: 99%
See 1 more Smart Citation